N-Doped carbon dots: a metal-free co-catalyst on hematite nanorod arrays toward efficient photoelectrochemical water oxidation. Issue 3 (23rd January 2017) - Huang, Xueni; Yang, Libin; Hao, Shuai; Zheng, Baozhan; Yan, Lei; Qu, Fengli; Asiri, Abdullah M.; Sun, Xuping
Abstract : N-Doped carbon dots (N-CDs) have been demonstrated as an effective co-catalyst for α-Fe2 O3 nanorod arrays on a Ti sheet for photoelectrochemical water oxidation. Abstract : In this communication, we demonstrate the use of N-doped carbon dots (N-CDs) as a co-catalyst for hematite (α-Fe2 O3 ) nanorod arrays on a Ti sheet for photoelectrochemical water oxidation. Under simulated light irradiation, the photocurrent density of the resulting N-CDs@α-Fe2 O3 /Ti as a photoanode exhibits a 3.4 times increase with a 280 mV cathode shift of the onset potential relative to that of pristine α-Fe2 O3 /Ti, with excellent photostability. The up-conversion fluorescent properties of N-CDs enable the absorption of longer wavelength irradiation with emission of short wavelength light to excite α-Fe2 O3, leading to the generation of more electron–hole pairs.